Аналіз роботи систем централізованого постачання тепла споживачам - Мартиняк, М. А.; Мисак, Й. С. (Видавництво Львівської політехніки, 2014)
Розглянуто методику розрахунку ефективності роботи систем централізованого теплопостачання на основі теплових балансів з врахуванням втрат тепла. Тhe article is devoted to the method of calculating the efficiency of district heating systems based on heat balance with regard to heat loss. Most of today district heating systems have a specific problem of technical wear and do not meet the modern technical level. In this connection there is a need in substantial capital investments for upgrading the boiler plants as well as networks for transportation of heat to the consumers. The method of analysis and calculation of the efficiency of energy systems without heat consumers and with heat consumers is proposed to analyze the performance of the systems and to determine the costs depending on the mode of operation and design features.
Keywords: система централізованого теплопостачання; теплові мережі; споживач тепла; коефіцієнт корисної дії; джерело генерації тепла; district heating system; heat networks; heat efficiency; the source of heat generation